2021
DOI: 10.1039/d1fo01887f
|View full text |Cite
|
Sign up to set email alerts
|

Borage oil intake by overweight young adults: no effect on metabolic rate; beneficial effects on plasma triglyceride and HDL cholesterol readings

Abstract: Some research has raised the possibility that gamma linolenic acid (GLA) can increase resting metabolic rate (RMR), which can help with weight control. However, in overweight young adults with a...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Some studies have shown that gamma-linolenic acid (GLA) can increase resting metabolic rate (RMR), which may help with weight control. However, no effect on RMR or body mass index was observed in overweight young adults with a family history of obesity [ 29 ]. A study by Khamaisi et al also showed insulin-sensitizing properties of GLA-alpha-lipoic acid conjugate associated with antioxidant activity [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have shown that gamma-linolenic acid (GLA) can increase resting metabolic rate (RMR), which may help with weight control. However, no effect on RMR or body mass index was observed in overweight young adults with a family history of obesity [ 29 ]. A study by Khamaisi et al also showed insulin-sensitizing properties of GLA-alpha-lipoic acid conjugate associated with antioxidant activity [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…The available literature shows that linoleic acid lowers blood cholesterol by 13.8%, as predicted by the Keys equation [ 28 ], while γ-linolenic acid lowers TG levels and raises HDL levels [ 29 ]. In an animal model, diets containing γ-linolenic acid from evening primrose oil also significantly reduced serum TG and TCH levels compared to other oils (palm and safflower) [ 30 ].…”
Section: Introductionmentioning
confidence: 99%